Efficacy of ensitrelvir against SARS-CoV-2 in a delayed-treatment mouse model. (2nd August 2022) - Nobori, Haruaki; Fukao, Keita; Kuroda, Takayuki; Anan, Naomi; Tashima, Ryoichi; Nakashima, Masaaki; Noda, Sayuri; Tajiri, Minako; Torii, Mikinori; Toba, Shinsuke; Uemura, Kentaro; Sanaki, Takao; et al.
Abstract: Objectives: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the aetiological agent of coronavirus disease 2019 (COVID-19) and a devastating worldwide health concern. Development of safe and effective treatments is not only important for interventions during the current pandemic, but also for providing general treatment options moving forward. We have developed ensitrelvir, an antiviral compound that targets the 3C-like protease of SARS-CoV-2. In this study, a delayed-treatment mouse model was used to clarify the potential in vivo efficacy of ensitrelvir. Methods: Female BALB/cAJcl mice of different ages were infected with the SARS-CoV-2 gamma strain (hCoV-19/Japan/TY7-501/2021) or mouse-adapted SARS-CoV-2 MA-P10 and then 24 h post-infection orally administered various doses of ensitrelvir or vehicle. Viral titres and RNA levels in the lungs were quantified using VeroE6/TMPRSS2 cells and RT–qPCR, respectively. Body weight loss, survival, lung weight, cytokine/chemokine production, nucleocapsid protein expression and lung pathology were evaluated to investigate the in vivo efficacy of ensitrelvir. Results: Based on infectious viral titres and viral RNA levels in the lungs of infected mice, ensitrelvir reduced viral loads in a dose-dependent manner. The antiviral efficacy correlated with increased survival, reduced body weight loss, reduced pulmonary lesions and suppression of inflammatory cytokine/chemokine levels. Conclusions: This was the first evaluation of the in vivo anti-SARS-CoV-2 efficacy of ensitrelvir in a delayed-treatment mouse model. In this model, ensitrelvir demonstrated high antiviral potential and suppressed lung inflammation and lethality caused by SARS-CoV-2 infection. The findings support the continued clinical development of ensitrelvir as an antiviral agent to treat patients with COVID-19.